Experimental study on dual-evaporator based microchannel flat loop thermosyphon (DE-MFLTS) waste heat recovery system. (November 2022) - Wang, Xupeng; Wen, Qiaowei; Wang, Xianling; Qiu, Zining; Wang, Zhangyuan; Shittu, Samson; Zhao, Xudong; Xiang, Jinwei; Weng, Chuangbin
Abstract: Multi-evaporator flat loop thermosyphon is multi-source heat exchange equipment with favourable application prospects in data centers. A new dual-evaporator microchannel flat loop thermosyphon (DE-MFLTS) system was presented in this article to improve the thermal environment of data centers. Two evaporators made of microchannel flat plates were innovatively installed inside the data cabinet to enable efficient and precise cooling for different servers, where the condenser is installed outside the data center room by a water-cooled separated loop construction. The temperature characteristics, heat recovery efficiency, and internal vapor pressure of the DE-MFLTS system were analyzed by experiments at various cooling water supply temperatures (from 15 °C to 24 °C) and various cooling water flow rates (from 200 l/h to 600 l/h) respectively. The two evaporators could maintain excellent temperature homogeneity under various operating conditions. The system demonstrated the best heat recovery efficiency of 82% under identical conditions when the cooling water supply temperature was 15 °C and the cooling water flow rate was 300 l/h. Compared with the single-evaporator system, the DE-MFLTS system had better performance in heat recovery efficiency. This research has significant implications for data centers' energy efficiency and emissions reduction.